Challenging undue influence? Rethinking children's participation in contested child contact. Issue 1 (2nd January 2021) - Tisdall, E. Kay M.; Morrison, Fiona; Warburton, Judy
ABSTRACT: Despite the widespread ratification of the United Nations Convention on the Rights of the Child, children continue to struggle to have their participation rights recognised and supported. This is evident within family law, where despite sometimes progressive and strong legislation, children's views are often not heard, nor given due weight, when parent-child contact is contested within the courts. This paper explores barriers to children's participation rights being realised. It uses Scotland as the example, due to its strong legal safeguards and mechanisms that aim to support participation rights. The paper draws on recent empirical research with legal professionals, combined with an analysis of reported case law and relevant literature, to explore the barriers 'on the ground' for children's participation rights. Through our analysis, we offer new ways to conceptualise the notion of influence in children's participation rights in family actions. We offer the conceptual devices of 'the influenced child' and 'the influential child' to elucidate how children's participation rights are restricted.